IN HOUSE TRAINING AND LEARNING MODELS AT SENIOR HIGH SCHOOL PULAU PUNJUNG DHARMASRAYA DISTRICT - Zulfa, Zulfa; Husnita, Liza; Saputra, Reski; Sebastianus, Sebastianus (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
In House Training (IHT) is a training conducted by the driving school in the Merdeka curriculum. One of the best driving schools is SMAN 1 Pulau Punjung. This IHT aims to refresh teachers considering the importance of using the right methods and the strategic position of the learning committee as a stimulant and initiator of change in the school environment. The method of implementing this activity is carried out to provide solutions in order to overcome partner problems. Through needs analysis, work plans, activity implementation, and evaluation. Activities realized in this community service include: providing material on In House Training Learning Models at SMAN 1 Pulau Punjung, Dharmasraya Regency. Based on the results of the In House Training (IHT) learning models for teachers of SMAN 1 Pulau Punjung, Dharmasraya Regency, it can be concluded that by increasing teachers' understanding of learning models, students' enthusiasm for learning will increase so that student learning outcomes will increase. The selected learning models, such as project-based learning, cooperative learning, and the use of technology in learning, aim to increase active student participation and 21st century skills. The results of this activity indicate that teachers of SMAN 1 Pulau Punjung have increased their competence in designing and implementing more creative learning models that are in accordance with the needs of students in the digital era.